Jacob Roland: um jesuíta flamengo na América Portuguesa - Juarez Donizete Ambires (Revista Brasileira de História, 2005)
Este artigo procura recuperar a figura do jesuíta flamengo Jacob Roland que, na América Portuguesa, foi missionário e, depois, apoio paulista na solicitação de administração direta do índio. This article brings up the Fleming jesuit Jacob Roland who, in the Portuguese America, was first a missionary and then a supporter of the request for direct administration of the indian peoples.